Anticonvulsant Potential of Essential Oil of Vetiveriazizanioides Linn. Nash - Kumar, Praveen; Tripathi, Laxmi (Asian Journal of Chemistry, 2013)
In light of the traditional claim of south Indian tribes to use root and stem juice of Vetiveria zizanioides (Linn.) Nash in the treatment of epilepsy, an investigation was carried out to evaluate the anticonvulsant activity of essential oil obtained from the fresh roots and stem of V. zizanioides. The anticonvulsant activity was screened in maximal electroshock induced seizure (MES) and subcutaneous pentylenetetrazole induced seizure models in mice. The neurotoxicity was assessed using the rotorod method. Oil obtained from roots of V. zizanioides showed 100 % protection in maximal electroshock induced seizures. But, no protection was observed in subcutaneous pentylenetetrazole induced seizures. Oil obtained from stems of V. zizanioides was inactive in both maximal electroshock and subcutaneous pentylenetetrazole induced seizures. No neurotoxicity was observed at the highest administered dose. Thus, the present study has demonstrated that the essential oil present in roots of V. zizanioides has anticonvulsant properties.